2007
DOI: 10.1038/nature05508
|View full text |Cite
|
Sign up to set email alerts
|

Importance of rain evaporation and continental convection in the tropical water cycle

Abstract: Atmospheric moisture cycling is an important aspect of the Earth's climate system, yet the processes determining atmospheric humidity are poorly understood. For example, direct evaporation of rain contributes significantly to the heat and moisture budgets of clouds, but few observations of these processes are available. Similarly, the relative contributions to atmospheric moisture over land from local evaporation and humidity from oceanic sources are uncertain. Lighter isotopes of water vapour preferentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
573
0
4

Year Published

2013
2013
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 449 publications
(609 citation statements)
references
References 23 publications
32
573
0
4
Order By: Relevance
“…In the meanwhile ground-based FTIR (Fourier Transform InfraRed) instruments (Schneider et al, 2006 have been used for measuring δD in the lower and middle troposphere. Furthermore, there are space-borne scientific sensors that measure middle tropospheric δD (Worden et al, 2007) and δD at and above the upper troposphere and lower stratosphere (e.g. Steinwagner et al, 2007;Payne et al, 2007;Lossow et al, 2011).…”
Section: A Wiegele Et Al: the Musica Metop/iasi H 2 O And δD Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meanwhile ground-based FTIR (Fourier Transform InfraRed) instruments (Schneider et al, 2006 have been used for measuring δD in the lower and middle troposphere. Furthermore, there are space-borne scientific sensors that measure middle tropospheric δD (Worden et al, 2007) and δD at and above the upper troposphere and lower stratosphere (e.g. Steinwagner et al, 2007;Payne et al, 2007;Lossow et al, 2011).…”
Section: A Wiegele Et Al: the Musica Metop/iasi H 2 O And δD Productsmentioning
confidence: 99%
“…But different effects on the energy budget are still not clear such as rainfall evaporation (e.g. Worden et al, 2007) or radiative impacts depending on the present water phase (e.g. Trenberth et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Because of saturation vapor pressure differences between heavy and light isotopologues, water vapor becomes depleted in isotopically heavy molecules during condensation and precipitation [Bigeleisen, 1961;Dansgaard, 1964]. As a result, stable isotope ratios in water help identify processes that moisten and dehydrate the atmosphere [Worden et al, 2007;Noone, 2012] and distinguish air masses by their integrated condensation histories [Gat, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…This method also has the large advantage of minimizing the error on the δD profile (e.g. Schneider et al, 2006) as demonstrated for example by Worden et al (2006Worden et al ( , 2007Worden et al ( , 2012 on TES measurements, on IASI measurements by Schneider and Hase (2011) and Lacour et al (2012), or for ground-based measurements by Schneider et al (2006Schneider et al ( , 2010Schneider et al ( , 2012.…”
Section: Particularity Of the δD Retrieval: The Hdo / H 2 O Correlatementioning
confidence: 99%
“…Worden et al, 2006Worden et al, , 2007 whereas the SCanning Imaging Absorption spectrometer for Atmospheric CartograpHY (SCIAMACHY) instrument provided total column distributions, with sensitivity down to the boundary layer (Frankenberg et al, 2009). Both TES and SCIAMACHY distributions required significant time averaging to reach the global scale, which puts a limit on what can be expected for monitoring the short-term variability of water.…”
Section: Introductionmentioning
confidence: 99%